Brainstem Raphe Alterations in TCS: A Biomarker for Depression and Apathy in Parkinson's Disease Patients - Richter, Daniel; Woitalla, Dirk; Muhlack, Siegfried; Gold, Ralf; Tönges, Lars; Krogias, Christos (Frontiers in Neurology, 2018)
Depression and apathy can both be present in patients with Parkinson’s disease (PD) while e.g. essential tremor (ET) patients mostly only report depressive symptoms. In PD, depression has been linked with brainstem raphe (BR) signal alterations in transcranial sonography (TCS) but apathy has not been evaluated in such terms as a putative biomarker. Furthermore, the BR has only been investigated using a singular axial TCS examination plane, although coronal TCS examination allows a much more accurate evaluation of the craniocaudal formation of serotonergic raphe structures in the midbrain area. The objective of this study was to investigate the value of coronal TCS examination for the detection of BR signal alterations and clinically correlate it to apathy in patients with PD, ET and healthy controls (HC). We prospectively included PD patients (n=31), ET patients (n=16) and HC (n=16). All were examined by TCS in the axial and coronal plane with focus on BR signal alterations. LARS and BDI-II scores were conducted to assess apathic and depressive symptoms in the study population. In a detailed analysis we found that the correlation of coronal and axial TCS alterations of BR was very high (rho=0.950, p<0.001). BR signal alterations were more frequent in PD patients than in ET patients and HC, while it was not different between ET patients and HC. In the PD patient group, BDI-II and LARS scores were negatively correlated to BR signal changes in TCS in a significant manner (BDI-II and axial BR: p=0.019; BDI-II and coronal BR: p=0.011; LARS and axial BR: p=0.017; LARS and coronal BR: p=0.023). Together in this brainstem ultrasound study we find a significant association of BR signal alterations with clinically evident apathy and depression in patients with PD. Therefore, TCS might enable the identification of a subgroup of PD patients which are at higher risk to suffer from or to develop depression or apathy.